Domestic politics and international narcotics control: U.S. relations with Mexico and Colombia, 1989 - 2000 - Hinojosa, Victor Javier (Studies in international relations, 2007)
Two-level games and international narcotics control -- The administration of President George Bush, 1989-1992 -- The first Clinton administration, 1993-1996 -- The second Clinton administration, 1997-2000 -- Conclusions